Financial times historical archive (Gale primary sources, 1888)
The Financial Times began as a City of London news sheet and grew to become one of the best-known and most-respected newspapers in the world. Along the way, the Financial Times - printed on its distinctive salmon-colored paper - has chronicled the critical financial and economic events that shaped the world, from the late nineteenth and entire twentieth centuries to today. This historical archive is a comprehensive, accurate, and unbiased research tool for those studying economic and business history and current affairs of the last 120 years. Initially focused on the global financial and economic issues that were to become the predominant forces of the twentieth century, the Financial Times expanded coverage in the postwar years, reporting on topics such as industry, energy, and international politics. In more recent decades, coverage of management, personal finance, and the arts has been added.An online, fully searchable facsimile, the Financial Times Historical Archive delivers the complete run of the London edition of this internationally known daily paper, from its first issue through 2010 (part 1) and through 2016 (part 2). Every article, advertisement, and market listing is included - shown both individually and in the context of the full page and issue of the day.